Assessment of risk of diabetes and knowledge regarding prevention of diabetes among office workers in Shillong, Meghalaya - Kakoti, Moutushi; Myrthong, Catharine Eva; Newar, Kalpana (International Journal Of Community Medicine And Public Health, 2025)
Background: Sedentary lifestyle of the office workers can be a crucial risk factor for developing diabetes. An early detection of risk for diabetes can be beneficial for participants to prevent occurring of diabetes and its serious complications. Therefore, this study assessed the risk of developing diabetes among office workers and their knowledge regarding prevention of diabetes. Methods: A cross-sectional study was conducted among 110 non-diabetic office workers in Shillong, Meghalaya, India, using purposive sampling, from 15 January to 10 February 2024. The risk for developing diabetes was assessed by the Indian diabetes risk score. Self-administered knowledge questionnaire was utilized to assess knowledge about diabetes prevention. Results: Majority of the participants (50.9%) were in the age group of 50 years and above, were female (51.8%), were graduates (60%), were residing in urban areas (63.6%), had a monthly income between Rs 73,054 to Rs 1,09,579 (44.5%) and were married (78.2%). A mean risk score of 53.27±19.49 indicated that the majority of office workers (52.7%) had a high risk for developing Diabetes. Most participants had average knowledge (47.3%) with a mean score of 7.92±2.54. A weak positive correlation was found between diabetes risk and knowledge, the association was not statistically significant (p=0.882), while knowledge of prevention was significantly associated with educational status (p≤0.05). Conclusions: The study emphasizes office workers’ knowledge on diabetes must be enhanced in order to prevent diabetes. Early diagnosis of the disease may prevent progression of disease and its complications.